Real-time flow impedance evaluation method for ultra-fast early detection of aneurysmal diseases. (February 2021) - Wong, Yoke Rung; Ong, Chi Wei; Toh, Alyssa LiYu; Lim, Einly; Ho, Pei; Leo, Hwa Liang
Highlights: Typical Diagnosis of aneurysmal diseases can only be done by routine medical tests. Inexpensive, less time consuming and technical demanding test is in demand. Real-time flow impedance was proposed to detect aneurysm. Features of real-time flow impedance were correlated with the aneurysm formation. Abstract: Objective: A novel method to measure the real-time input flow impedance of thoracic aorta aneurysm (TAA) was developed. Methods: The fundamental of real-time input flow impedance was described. The simultaneously measured blood pressure and volumetric flow rate were obtained and used for the calculation. The input flow impedance was then presented in its complexed format: real and imaginary; modulus and phase in the time domain. Results: Unique features of real-time input flow impedance were extracted to correlate with the TAA formation. It showed that the trough of modulus located at the end of each cardiac cycle has different values, which are proportional to the sizes of TAAs. Conclusions: A real-time input flow impedance of the cardiovascular system was presented in this paper. We postulate that the proposed fluid mechanics model has the potential to analyze the pathomechanics of aneurysmal diseases in real-time.